Boundary Dynamics in Natural Resource Management: The Ambiguity of Stakeholder Inclusion - Prins, Sylvia; Craps, Marc; Taillieu, Tharsi (Revue Gouvernance / Governance Review, 2005)
This paper discusses a case study in the domain of water management and nature conservation from the perspective of boundary dynamics. Multiparty collaboration is proposed as an organizational strategy to manage natural resources. This approach acknowledges the multiple perspectives of stakeholders, the differences in interest and power, and it provides a strategy for change in a domain with a high potential for conflict (Buckles, 1999). The first part of the paper outlines the theoretical insights and frames that underpin the case analysis. Then it discusses boundary issues in a project set up to design a plan for a river valley to solve problems of flooding and deterioration of nature. With this in-depth case study in a complex organizational setting we aim to contribute to empirical research on the perceptions of boundaries in processes of organizing (Paulsen & Hernes, 2003).